Understanding the Blood-Brain Barrier (BBB) with MRI Techniques and Its Implications in Neurodegenerative Diseases: An Overview - Oliveti, Cesare; Iacomino, Aniello; Manti, Francesco; Tinelli, Emanuele; Gatta, Gianluca; Di Grezia, Graziella; Cascini, Giuseppe Lucio; Cuccurullo, Vincenzo (Trends in Sciences, 2024)
The blood-brain barrier (BBB) stands as a critical guardian separating the central nervous system (CNS) from the systemic circulation. This comprehensive review explores the anatomical and functional components of the BBB and its association with the neurovascular unit (NVU), emphasizing its role in synaptic signaling and shielding the CNS from neurotoxic elements. Detailed discussions encompass MRI techniques like dynamic contrast enhancement (DCE) and arterial spin labeling (ASL) MRI, illuminating their significance in assessing BBB integrity and permeability. Various models and pharmacokinetic parameters utilized in imaging analysis offer insights into barrier permeability, aiding in the evaluation of neurodegenerative illnesses such as Alzheimer’s, Parkinson’s, and multiple sclerosis. Additionally, the study investigates the distinct characteristics of imaging protocols and their impact on BBB evaluation. Highlighting physiological conditions, the analysis discerns regional disparities in BBB permeability, shedding light on diverse microvascular architectures in healthy subjects. Conversely, in pathological states like Alzheimer’s, Parkinson’s, and multiple sclerosis, BBB dysfunction leads to a cascade of events facilitating the entry of harmful substances, exacerbating neurodegeneration. Imaging studies have unveiled distinct alterations in BBB permeability and perfusion, providing crucial insights into disease progression, notably preceding structural changes in Alzheimer’s and indicating localized disruptions in multiple sclerosis. This comprehensive exploration underscores the pivotal role of the BBB in maintaining CNS health and its intricate involvement in the pathogenesis of neurodegenerative disorders. While imaging techniques serve as promising tools for BBB assessment, further research is warranted to refine their diagnostic precision and differentiation abilities across neurological conditions. HIGHLIGHTS The central role of the blood-brain barrier (BBB) with its anatomical-functional components and the association with the neurovascular unit (NVU) represent the heart of this study whose aim is to evaluate and be able to grasp the pathological alterations of permeability and perfusion that suggest the existence of neurodegenerative diseases such as Alzheimer’s, Parkinson’s and multiple sclerosis. Different MRI techniques that are used to evaluate BBB alterations such as dynamic contrast enhancement (DCE), MRI with arterial spin labeling (ASL) and various pharmacokinetic models and parameters will be discussed through a literature review in order to provide the radiologist and clinician clear indications regarding the main techniques suggested in the evaluation of this important anatomical-functional unit. GRAPHICAL ABSTRACT